In silico analysis of RNA-dependent RNA polymerase of the SARS-CoV-2 and therapeutic potential of existing antiviral drugs - Mondal, Sunil Kanti; Mukhoty, Samyabrata; Kundu, Himangsu; Ghosh, Subhajit; Sen, Madhab Kumar; Das, Suvankar; Brogi, Simone (Computers in biology and medicine, 2021)
The continued sustained threat of the SARS-CoV-2 virus world-wide, urgently calls for far-reaching effective therapeutic strategies for treating this emerging infection. Accordingly, this study explores mode of action and therapeutic potential of existing antiviral drugs. Multiple sequence alignment and phylogenetic analyses indicate that the RNA-dependent RNA polymerase (RdRp) of SARS-CoV-2 was mutable and similar to bat coronavirus RaTG13. Successive interactions between RdRp (nsp12 alone or in complex with cofactors nsp7-8) and viral RNA demonstrated that the binding affinity values remained the same, but the sites of interaction of RdRp (highly conserved for homologous sequences from different organisms) were altered in the presence of selected antiviral drugs such as Remdesivir, and Sofosbuvir. The antiviral drug Sofosbuvir reduced the number of hydrogen bonds formed between RdRp and RNA. Remdesivir bound more tightly to viral RNA than viral RdRp alone or the nsp12-7-8 hexadecameric complex, resulting in a significant number of hydrogen bonds being formed in the uracil-rich region. The interaction between nsp12-7-8 complex and RNA was mediated by specific interaction sites of nsp7-8. Therefore, the conserved nature of RdRp interaction sites, and alterations due to drug intervention indicate the therapeutic potential of the selected drugs. In this article, we provide additional focus on the interacting amino acids of the nsp7-8 complex and highlight crucial regions that could be targeted for precluding a correct recognition of subunits involved in the hexadecameric assembly, to rationally design molecules endowed with a significant antiviral profile.
Keywords: Antiviral Agents; COVID-19; Phylogeny; lidé; RNA-dependentní RNA-polymerasa; SARS-CoV-2; antivirové látky; RNA-Dependent RNA Polymerase; fylogeneze; Humans; počítačová simulace; Computer Simulation